2022
DOI: 10.31925/farmacia.2022.2.4
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENT AND CHARACTERIZATION OF LORATADINE LIPOSOMAL GEL USING QbD APPROACH

Abstract: This study aimed to formulate, prepare and characterize a loratadine liposomal gel (LOR-L-G) using the Quality by Design (QbD) approach. The formulation variables and process parameters that influence the Critical Quality Attributes (CQAs) were identified using risk assessment. Five dependent variables were considered relevant for this study: particle size before and after extrusion, polydispersity index (PDI) before extrusion, loratadine (LOR) concentration and encapsulation efficiency (EE). A two-level full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The QbD risk assessment implies an interdependence rating established between the CMAs-CQAs and/or CPPs-CQAs, measuring the impact of each quality attribute on the final product [32,33]. Risk estimation matrix (REM) is a risk rating tool constructed for CMAs and/or CPPs commonly using a three-grade scale (low, medium and high) to describe the criticality in relation to the CQAs [34].…”
Section: Risk Assessmentmentioning
confidence: 99%
“…The QbD risk assessment implies an interdependence rating established between the CMAs-CQAs and/or CPPs-CQAs, measuring the impact of each quality attribute on the final product [32,33]. Risk estimation matrix (REM) is a risk rating tool constructed for CMAs and/or CPPs commonly using a three-grade scale (low, medium and high) to describe the criticality in relation to the CQAs [34].…”
Section: Risk Assessmentmentioning
confidence: 99%
“…All these characteristics were chosen to obtain a favourable sensory profile for increased patients’ acceptability, taking into consideration the longer period of use in seborrheic dermatitis. Table 9 contains the QTPP and QAs considered relevant for this study, which were established based on previously reported studies that use similar settings [ 14 , 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each of these criteria was attributed to each CPP (formulation factors and process parameters) and was ranked from 1 to 5 on a scale: the occurrence (O) was evaluated as 5 for frequent, 4 for probable, 3 for occasional, 2 for remote, and 1 for improbable; the severity (S), was ranked as 5 for catastrophic, 4 for critical, 3 for serious, 2 for minor, and 1 for negligible; detectability (D) was given a score of 5 for hard to detect, 4 for low chance of detection, 3 for moderately detectable, 2 for highly detectable, and 1 for easily detectable. The risk score has been revealed as risk priority number (RPN), by multiplying these three attributes [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…The total volume was modified to 100 ml by purified water including LORA-NLCs. The gel was left overnight in the refrigerator, LORA-NLCs Ocugel had a final concentration of 1 mg/g LORA (Toma et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%